Factors Related to Science Achievement of Mathatomsuksa 3 Students - Insumran, Sutarose; Srihaset, Kamontip; Tippayakulpairoj, Duranee (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Learning science is important for students because it is a subject that helps them think creatively, think logically, think systematically, and have a plan be able to analyze problems or situations thoroughly. However, science learning achievement is influenced by many factors. Therefore, to obtain information that can be used in planning science learning, and use it as a solution that will enable students to develop their academic achievement in science to their full potential. Therefore, this research has the objectives to: 1) study the factors that are related to academic achievement in the science of Mathayomsuksa 3 students and 2) create an equation to predict the academic achievement in science of a sample group of Mathayomsuksa 3 students. Methodology: There were 498 Mathayom 3 students, which were obtained from multi-stage sampling. Data was collected using questionnaires. The data was analyzed using multiple regression analysis. Results: 1) The correlation coefficient (R) between the dependent variables is academic achievement in science subjects and the independent variables; sex, basic knowledge in science scientific, attitudes toward learning science, perception of scientific competence, teacher support, parents' support for science learning, peer support in learning science, study atmosphere and responsibility for learning science is equal to 0.92. The set of independent variables can explain 84.30 percent of the variance in the dependent variable (R2). 2) The independent variable that has the greatest relationship with academic achievement in science is basic knowledge in science. (b=0.90), followed by science learning attitude (b=0.10), teacher support (b=0.07), study atmosphere (b=0.06), and gender (b=0.05), respectively, by the factor prediction equation that has a relationship with academic achievement learning science subjects of Mathayom 3 students by selecting variables into the equation using the Enter format found that the regression coefficient (b) of sex, basic knowledge in science scientific, attitudes toward learning science, teacher support and study atmosphere were statistically significant at the .05 level. The relationship could be written in a prediction equation in the raw score as follows: = 38.54 + 0.96sex*+11.58basic knowledge in science scientific* +1.65attitudes toward learning science*-1.21 teacher support* –0.90classroom atmosphere* Conclusion: Research reveals a strong relationship between science achievement and a set of influential independent variables that explain a significant portion of the overall variance. Basic science knowledge was considered the most important factor, followed by positive science learning attitude, teacher support, learning environment, and gender. These findings provide valuable insights into the determinants of academic success in science among Mathayom 3 students, highlighting the importance of basic knowledge and a positive attitude towards learning.